Exploring Perspectives of Undergraduate Students on Contributions of Social-Media towards Their Enhanced Academic Growth - Zada, Ahmad; Abdul Latiff Tarique, Azmi; M. Anthony, Elizabeth (Development in Language Studies, 2023)
Social-media appears to be rapidly gaining popularity in this "technology era," particularly among university students. The purpose of the study was to study and analyze the impact of social media on the academic performance of undergraduate students and to give recommendations regarding the use of social media for the betterment of academic performance. The study was performed using the qualitative method. Data were collected from 14 undergraduate students from different departments through interviews using a purposive sampling technique. Seven research questions guided the study. The data were analyzed through tabulation of frequency and percentage and the thematic analysis-based research findings showed that using social media negatively affects the academic performance of undergraduate students. This study further revealed that using social media has positive effects on undergraduates’ assignments and using social media has negative effects on the health and physical activities of the undergraduate students.